Analisa Kepuasan Pengguna Sistem Informasi Manajemen Rumah Sakit Menggunakan Metode EUCS - Fyna Febrianti (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The Hospital Management Information System (SIMRS) is a system applied to the Tampan Mental Hospital (RSJ Tampan) Riau Province which is used as a communication line between service centers and processes data and information so that it can be used for hospital decision making and is a Local Area Network . During implementation, SIMRS still has several problems including features with data that are out of sync, the color composition displayed is not attractive, there are still users who have difficulty processing information data and the slow response of the system at certain times. This study uses the End User Computing Satisfaction (EUCS) method which has 5 main dimensions, namely Content, Accuracy, Format, Ease of Use and Timeliness. Data collection using the Saturation Sampling model with 100 respondents obtained through the distribution of questionnaires, interviews, and observations, processed using SmartPLS version 3.0. The results of this study indicate that user satisfaction with SIMRS reaches 73.4% where this number indicates that users are satisfied with SIMRS. Regarding some of the problems experienced by users, the researcher provides 4 recommendations for improvements so that SIMRS can run optimally and not too time consuming.